Factors associated with hypertension in women of child-bearing age in Abeokuta - Oluwafunke O. Akinbule; Kindness L. Okekhian; Adebukola T. Omidiran; Sultan A. Adenusi; Oluwadamilola T. Lasabi; Catherine A. Oladoyinbo (Human Nutrition & Metabolism, 2022)
Background: Maternal diet quality, obesity, and abdominal obesity are known risk factors for hypertension in women. Objectives: This study assessed the factors associated with hypertension in women of child-bearing age in Odeda local government area communities, Abeokuta. Methods: A cross-sectional survey was conducted on 250 women (18–49 years) using systematic random sampling. Information on dietary intake was obtained using a 24-h dietary recall questionnaire. Food consumption (FCS), food variety (FVS), and dietary diversity scores (DDS) were assessed using validated questionnaires. Blood pressure, weight, height, waist and hip circumferences were assessed using standard procedures. Data were presented with frequency, percentage, median, interquartile range, and binary logistic regression was used to test for associated factors with hypertension at p < 0.05. Results: Almost one-quarter (22.8%) of the respondents had acceptable FCS, about one-third (30.4%) achieved the minimum DDS and 46.8% had good FVS. Most respondents had inadequate intakes of fat, fibre, vitamins A, C, B1, B6, folate, calcium, sodium, potassium and magnesium. The prevalence of hypertension, overweight, obesity and abdominal obesity were 28.8%, 28.0%, 9.2%, and 80.0%, respectively. Unacceptable FCS (OR = 0.37, 95% CI: 0.19–0.71), and increasing BMI (OR = 3.6, 95% CI: 1.97–6.60) were significantly associated with hypertension. Conclusion: Respondents had low diet quality, high prevalence of overweight and hypertension. Increasing BMI, and unacceptable FCS were associated with hypertension.